Retention of anticancer activity of curcumin after conjugation with fluorescent gold quantum clusters: an in vitro and in vivo xenograft study - Khandelwal, Puneet; Alam, Aftab; Choksi, Arpankumar; Chattopadhyay, Samit; Poddar, Pankaj (ACS Omega, 2018)
Gold nanoparticles (Au NPs) have been thoroughly investigated for anti-cancer therapy. However, their undesired high gold content remains a problem when injected into the body for drug delivery applications. In this report, we made an effort to conjugate the curcumin molecules on the surface of gold quantum clusters (Au QCs) by a novel in situ synthesis method which provides an alternative route to not only reduce the metallic content but also increase the water solubility of curcumin and the loading efficiency. Here, curcumin itself acts as a reducing and capping agent for the synthesis of Au QCs. The UV−vis absorption, fluorescence, transmission electron microscopy, and electrospray ionization mass spectrometry results confirmed the synthesis of fluorescent Au QCs. Curcumin-conjugated Au NPs (C-Au NPs) and glutathione (GSH)-conjugated Au QCs (GSH-Au QCs) were also synthesized to visualize the effect of particle size and the capping agent, respectively, on the cytotoxicity to normal and cancer cells. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that the curcumin-conjugated Au QCs (C-Au QCs) were less cytotoxic to normal cells while almost the same cytotoxic to cancer cells in comparison to curcumin itself, which indicates that curcumin preserves its anticancer property even after binding to the Au QCs. However, C-Au NPs and GSH-Au QCs did not show any cytotoxicity against the normal and cancer cells at the concentration used. The western blot assay indicated that C-Au QCs promote apoptosis in cancer cells. Further, the in vivo study on severe combined immunodeficiency mice showed that C-Au QCs also inhibited the tumor growth efficiently without showing significant toxicity to internal organs.